Safeguarding energy tunnels against explosive load by using concrete and soil annihilators - Hassanpour, Mahmood Reza Toloue; Movahedifar, Seyed Mojtaba (Ciência e Natura, 2015)
Utilization of buried structures is one of the usual approaches of non-factor defense in order to protect vital plants and arteries of cities against terroristic attacks (explosion). Besides the examination of the effect of surface and deep explosions on buried structures and how to model and analyze them in Abaqus software and in 3D mode, this study investigates various strategies to improve their safety. In this investigation, the influence of using concrete annihilators made horizontally on the upper surfaces of tunnels is examined. In addition, the improvement of the performance of these structures by using soft sand vertical sinks that are able to be made around energy tunnels, is examined. Investigations show that although using anti-explosion eagles reduces the damages of explosive loads, using mixed annihilators may effectively improve this performance.